Augmented healing of full thickness chronic excision wound by rosmarinic acid loaded chitosan encapsulated graphene nanopockets. (2nd June 2020) - Chhabra, Priyanka; Chauhan, Gaurav; Kumar, Amit
Abstract: Nanoparticles have emerged as an important carrier system to treat wounds as they permit the topical administration of an antimicrobial drug in a sustained and effective manner. On the other hand, if active excipients are added during the formulation, such as chitosan or graphene oxide, the developed Nano formulation could significantly improve its potential for chronic wound healing. Given that, we have conceived the fabrication and evaluation of rosmarinic acid loaded chitosan encapsulated graphene nanoparticles (RA-CH-G-NPOs) formulation to enhance wound healing capacity. The prepared nanoparticles were characterized by particle size, Zeta potential, FT-IR, SEM, TEM and AFM. It was observed the average diameter of RA-CH-G-NPOS is around 417.5 ± 18.3 nm and showed sustained release behavior. Optimized RA-CH-G-NPOs were incorporated into Carbopol gel and evaluated for drug content, pH, in vitro release, texture analysis, and viscosity. The antibacterial activity of optimized formulation was examined as a minimum inhibitory concentration against Staphylococcus aureus . The fabricated RA-CH-G-NPOs were than evaluated for in vitro antimicrobial activity by microdilution assay The combination of RA, Chitosan and Graphene oxide (GO) showed higher antibacterial activity of 0.0038 ± 0.2 mg/mL. Further, these nanoparticles were evaluated in- vivo for wound healing efficacy in Sprague Dawley rats. Histopathological evaluations demonstrated that RA-CH-G-NPOs showed significantly enhanced wound contraction, enhanced cell adhesion, epithelial migration, and high hydroxyproline content leading to faster and more efficient collagen synthesis as compared to plain carbopol, plain RA and controls. Hence the topical administration of fabricated RA-CH-G-NPOs appears to be an interesting and suitable strategy for the treatment of chronic wounds.